Development of Visual Information-Based Teaching Materials to Enhance Reading Skills in English Language Learning - Putri Asilestari; Zalisman Zalisman; Sri Wahyuni; Nurhidayah Sari (JETL (Journal of Education, Teaching and Learning), 2025)
This study aims to develop valid, practical, and effective reading materials based on visual information for the English Education Program. The study is motivated by the lack of reading materials that utilize visual information in English language learning. The research uses the ADDIE development model, with data collection methods including observation, interviews, and documentation studies. The data obtained were analyzed using the SPSS software. The results show that: (1) in the analysis phase, a pressing need for the development of reading materials based on visual information to improve students' reading skills was identified; (2) in the design phase, the learning materials and visual information design received excellent ratings in accordance with the curriculum requirements and student characteristics; (3) in the development phase, the visual information book and its supporting system met high criteria for validity, practicality, and effectiveness; (4) in the implementation phase, the application of visual information had a positive impact on improving students' reading skills; (5) effectiveness testing showed that the use of visual information in reading skill learning was effective, with the t-test results showing that the t-value (4.697) was greater than the t-table value (1.69) and the significance level was less than 0.05 (0.000). In conclusion, the use of reading materials based on visual information has been proven to improve students' reading skills, showing a significant difference between the experimental group using visual information and the control group not using visual information